Samostigma med strokovnjaki na področju duševnega zdravja v Sloveniji – izsledki pilotne študije - Roškar, Saška (Psihološka obzorja (Ljubljana), 2024)
Public and self-stigma substantially hinder seeking of help during times of psychological distress. Stigma can occur during mental illness or be anticipated when mental illness is not yet present. An important and vulnerable group, but one that is often neglected, are professionals working in mental health field. Using a sample of mental health professionals from Slovenia (N = 93), we focused on the relationship between personal experiences of mental disorders and suicidal behavior and different types of anticipated self-stigma (mental illness and help-seeking self-stigma). About half of the participants (49%) had past or current experience of mental illness, and 56% of them sought help. One sixth of participants (16%) reported having had suicidal ideation in the past or currently, but only 20% sought help for this. Gender was not significantly related to any type of stigma. Age was negatively correlated with personal experience of mental illness and anticipated self-stigma of mental illness. Individuals with personal experiences of mental illness showed higher self-stigma of mental illness than individuals without such experiences. Self-stigma of mental illness correlated slightly with self-stigma in help-seeking. Based on the results we conclude that in mental health professionals, experiences with one’s own mental health issues are related to higher self-stigma of mental illness and this is related to higher self-stigma in help-seeking. Hence, specific interventions should be developed to destigmatize mental illness among professionals and promote help-seeking in this group. Further research is warranted.
Keywords: duševno zdravje; experts; help seeking; iskanje pomoči; mental health; samostigma; self-stigma; strokovnjaki; The self-stigma of mental illness SSOMI; The self-stigma of seeking help SSOSH; Vprašalnik samostigme duševnih bolezni SSOMI; Vprašalnik samostigme iskanja pomoči SSOSH